The Role of Mistrust in Sexual Revictimization: An Analysis of Serial Indirect Effects - Lutz-Zois, Catherine J. (Violence against women, 2024)
A sample of 819 female college students completed measures of childhood sexual abuse (CSA), adult sexual victimization (ASV), mistrust, trauma-related symptoms, and drinking problems. Using a serial indirect effects model, we hypothesized that CSA would be associated with ASV through the indirect effects of mistrust → trauma-related symptoms → drinking problems. The results indicated that this serial indirect effects model was significant. When the order of the first two indirect effects was reversed, the model was not significant. These results highlight the importance of examining potential factors involved in sexual revictimization in tandem rather than in isolation.